Prices vs. Quantities vs. Laissez-faire - Browning, Martin (Review of Economic Studies, 1987)
Journal Article Prices vs. Quantities vs. Laissez-faire Get access Martin Browning Martin Browning McMaster University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 54, Issue 4, October 1987, Pages 691–694, https://doi.org/10.2307/2297490 Published: 01 October 1987 Article history Received: 01 December 1986 Accepted: 01 March 1987 Published: 01 October 1987